A Clock Synchronization Circuit Using Transmitted Time Codes - Bhat, C.L.; Razdan, H. (Defence Science Journal, 2014)
In this paper a logic circuit for digital clocks is discussed. Using high frequency radio time signals, it corrects errors upto Plus Minus 30 seconds with an accuracy of a millisecond. The circuit also monitors the clock errors, using the time display unit of the clock itself, and carries out synchronization even in relatively noisy reception conditions.